Conjunctival stromal tumour: A case report - Jane E. Buys; Christiaan H. Gouws; Stefanus W.D. van der Walt; Jacqueline Goedhals (Elsevier, 2024)
Conjunctival stromal tumour (COST) is a rare and newly described mesenchymal tumour of the conjunctiva. We present a case of a slow-growing conjunctival lesion in a 54-year-old female. Due to persistent irritant symptoms, the lesion was excised. Histopathological assessment showed a paucicellular tumour set in an oedematous and collagenous background within the lamina propria. Significant nuclear degenerative atypia was noted. Lesional cells were positive for CD34 immunohistochemistry. The features were consistent with COST. The condition is typically unilateral and arises in the bulbar conjunctiva, with both inflammatory and neoplastic origins considered. They are sporadic and occur most frequently in adults. COSTs are indolent and managed effectively with complete surgical excision. Conjunctival myxoma is the most important differential diagnosis due to its association with the Carney complex, a potentially life-threatening condition that requires close clinical follow-up. Accurate recognition of COST and myxoma is crucial to stratify care appropriately.